Rancang Bangun Sistem Informasi Pencatatan Inventarisasi Peralatan Berbasis Website di Koperasi Usaha Bersama Gabungan Baraya Suci - Hasan, Muhamad Nur; Mu'minin, Ayi Mi'razul (Jurnal Dimamu, 2025)
The Baraya Suci Joint Business Cooperative is one of the cooperatives that has several business divisions. In order to improve equipment recording, the author designed and developed a Website-based equipment ineventarization recording information system. The creation of the Web-Based Equipment Inventory Recording Information System report at the Joint Venture Cooperative of Baraya Suci is designed to help record equipment so that it can be known at any time and avoid data duplication and data loss. This Final Project was made based on the description method approach in collecting data and information needed to interpret objects systematically, factually, accurately and in accordance with the facts. Meanwhile, the system design uses the OOAD (Object Oriented Analysis Design) method with the UML (Unifed Model Languange) model. With this system, it can help the Baraya Suci Joint Business Cooperative in recording equipment in a more orderly, productive, efficient manner and can also provide information in real time.